Teachers Pedagogical Competence in Terms of Supervisors Academic Supervision and Teaching Experience - Sappaile, Baso Intang; Abeng, Andi Tenri; Nuridayanti, Nuridayanti (Journal International of Lingua and Technology, 2023)
" This study aims to determine the pedagogical competence of teachers in terms of supervisors' academic supervision and teachers' teaching experience. This type of research is ex post facto which consists of two independent variables, namely supervisor academic supervision (X1) and teacher teaching experience (X2) and one dependent variable, namely teacher pedagogical competence (Y). The study population was all private junior high school teachers in Binamu District, Jeneponto Regency. Class random sampling and the number of samples used Slovin. Data collection techniques are divided into two, namely questionnaires for variables X1 and X2 and tests for variable (Y). The results of the study found that: 1) teachers' pedagogical competence is influenced by supervisors' academic supervision and teachers' teaching experience, both jointly and partially.